Pengaruh Gaya Beajar terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Terpadu di SMP Negeri 8 Kota Gorontalo - Mutia Lestari Hasan; Melizubaida Mahmud; Agil Bahsoan; Radia Hafid; Rierind Koniyo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aimed to disclose the influence of learning style on student learning outcomes in integrated social studies subjects at SMP N 8 Kota Gorontalo. This quantitative research involved 64 samples, which were given questionnaires as instruments. The data in this study were analyzed using simple linear regression. Based on the analysis, there was a significant influence between the learning style and learning outcomes of grade VIII students at SMP Negeri 8 Kota Gorontalo. The influence of learning style on learning outcomes was 73.2%, and unexamined variables influenced 26.8%.